Numerical simulation of a vertical axis wind turbine airfoil experiencing dynamic stall at high Reynolds numbers. (13th June 2017) - Hand, Brian; Kelly, Ger; Cashman, Andrew
Highlights: Dynamic stall simulation of a VAWT NACA0018 airfoil during Darrieus pitching motion. Quantitative comparison of CFD modeling methods with experimental data. Dynamic stall vortices develop and are shed from the airfoil trailing edge region. Increasing the Reynolds number delays dynamic stall to greater angles of attack. Abstract: Multi-megawatt floating vertical axis wind turbines (VAWTs) are a promising solution to exploit offshore wind energy resources in deep water sites. At this large-scale, the VAWT's blades will operate at high Reynolds numbers and encounter dynamic stall at low tip-speed ratios. In particular, the selection of an accurate turbulence modeling approach is still a challenging undertaking in the prediction of transient blade forces during this complex unsteady event. In the present paper, the performance of Unsteady Reynolds-Averaged Navier–Stokes (U-RANS) and Detached Eddy Simulation (DES) modeling methods are compared in simulating the aerodynamics of an isolated NACA0018 airfoil experiencing Darrieus pitching motion. The U-RANS turbulence models employed were the Spalart–Allmaras (S-A) model and the k − ω SST model. Investigations were conducted to ensure satisfactory independency of the solution for both spatial and temporal discretisations, respectively. A quantitative assessment identified the S-A model as the most applicable for a VAWT design study as it showed the most desirable compromise between model fidelity and computational requirement. A qualitative analysis revealed that the thick VAWT airfoil creates a dynamic stall vortex topology highly concentrated at the trailing edge region. Finally, increasing the Reynolds number showed to be beneficial to the airfoil's aerodynamic performance as a higher maximum tangential coefficient is attained, owing to the delay in flow separation to much higher angles of attack.